RANCANG BANGUN MESIN PENGOLAH LIMBAH PERTANIAN UNTUK PRODUKSI PAKAN TERNAK AWETAN DI DAERAH KERING - Endaryanta, Endaryanta; Marsudi, Ilham; Sumardjito, Sumardjito; Purwoko, Bambang Setyo Hari (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2011)
Sukorejo village, Musuk, area at Boyolali is dry farm field, whereas this field is a breeder center of milking-cow and flesh-cows. They give food to cattle by traditional method, that is the grass is cut by knife and then give directly to the animals. In wet season, this method is no problem, but in dry season this method makes a problem because there are not easy to get much grass  for  cattle.  Consentrate  mill  and  rice  siftings  are  become  food substitution from its food although with high price. It is really, whereas agricultural rubbish (e.g.: stick of tuberous plant, stick of papaw, "lamtoro" stick, etc.) are in stock very much. Truly, this agricultural rubbish can be changed (by choping) become weft cattle. To solving this problem, team PPM FT UNY give a solution by making a manufactured agricultural rubbish machine and application of a silase  complete  weft  cattle  preserve  technology for  farmer  and  breeder group.   The PPM used several methods : presentation, trained, practiced, and made manufactured agricultural rubbish machine. The topic of training is complete weft cattle preserve technology (fermentation method), machine operation, safe and true maintenance of machine. The results of this PPM speciality programm  are : (1) farmer and breeder get 1 unit manufactured agricultural rubbish machine; (2) farmer and  breeder  get   a  skill  about   silase  complete  weft   cattle  preserve technology; and (3) they have could change agricultural rubbish become weft cattle, so it can increase of their grade prosperity